2017
DOI: 10.1167/iovs.16-20986
|View full text |Cite
|
Sign up to set email alerts
|

Gene Augmentation Therapy for a Missense Substitution in the cGMP-Binding Domain of Ovine CNGA3 Gene Restores Vision in Day-Blind Sheep

Abstract: PurposeApplying CNGA3 gene augmentation therapy to cure a novel causative mutation underlying achromatopsia (ACHM) in sheep.MethodsImpaired vision that spontaneously appeared in newborn lambs was characterized by behavioral, electroretinographic (ERG), and histologic techniques. Deep-sequencing reads of an affected lamb and an unaffected lamb were compared within conserved genomic regions orthologous to human genes involved in similar visual impairment. Observed nonsynonymous amino acid substitutions were clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Promising results have been replicated in the Awassi sheep model of CNGA3-ACHM, where gene therapy led to an improvement in the cone ERG and daylight vision, with effects maintained for up to three years post-treatment [70]. A more recent study has similarly shown rescue with gene therapy in the Awassi model [71]. The success of gene therapy in this case is of particular significance, since it occurred in a large animal model with a genotype in keeping with majority of CNGA3-ACHM genotypes (missense variants) rather than knock-out/premature termination models.…”
Section: Current Management and Pre-clinical Therapeutic Approachesmentioning
confidence: 89%
“…Promising results have been replicated in the Awassi sheep model of CNGA3-ACHM, where gene therapy led to an improvement in the cone ERG and daylight vision, with effects maintained for up to three years post-treatment [70]. A more recent study has similarly shown rescue with gene therapy in the Awassi model [71]. The success of gene therapy in this case is of particular significance, since it occurred in a large animal model with a genotype in keeping with majority of CNGA3-ACHM genotypes (missense variants) rather than knock-out/premature termination models.…”
Section: Current Management and Pre-clinical Therapeutic Approachesmentioning
confidence: 89%
“…Two spontaneous sheep models of Cnga3 achromatopsia have been identified [83]. The first identified has a nonsense mutation (p.Arg236Ter) and the second a missense mutation (p.Gly540Ser) [84]. Adeno-associated virus gene therapy was able to restore cone function in both models [84,85].…”
Section: Cnga3mentioning
confidence: 99%
“…This autosomal recessive hereditary disease was determined to be caused by a C → T substitution leading to a premature stop codon at residue 236 of the ovine CNGA3 gene (c.706C > T, p.R236*), thus making affected sheep a naturally-occurring large animal model for human CNGA3 ACHM 32 . Later, a second (missense) mutation resulting in day blindness in sheep was identified in the same gene (c.1618G > A, p.Gly540Ser) 33 . Like most non-primate mammals, the retina of a sheep contains a specialized region called an “area centralis”, rather than a fovea.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, we used these CNGA3 mutation models for successful gene therapy trials, based on subretinal injections of an adeno-associated virus carrying the CNGA3 transgene under the control of a cone-specific promoter 33 , 36 , 37 . Treatment restored cone function and photopic (daytime) vision within a few days in all treated sheep, as demonstrated both behaviorally and electroretinographically (ERG), with the oldest treated sheep still visual after more than 9 years 38 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation